Procalcitonin Differs in Children With Infection and Children With Disease Flares in Juvenile Idiopathic Arthritis. Issue 3 (April 2021) - Trachtman, Rebecca; Murray, Elizabeth; Wang, Cindy M.; Szymonifka, Jackie; Toussi, Sima S.; Walters, Heather; Nellis, Marianne E.; Onel, Karen B.; Mandl, Lisa A.
Abstract : Background/Objective: Patients with juvenile idiopathic arthritis (JIA) often present with signs and symptoms suggestive of serious bacterial infection (SBI). Procalcitonin (PCT) is a biomarker that is elevated in SBI. We conducted a comparative cohort study to test the hypothesis that PCT levels will differ between active JIA, quiescent JIA, and bacteremic patients and healthy controls. Methods: From October 2016 to May2018, consecutive children 6 months to 18 years of age with ( a ) active untreated JIA, ( b ) quiescent JIA, and ( c ) healthy elective presurgical candidates were recruited from clinics at a musculoskeletal specialty hospital. Juvenile idiopathic arthritis was defined according to the International League of Associations for Rheumatology criteria. Clinical data and serum samples meeting the same criteria were included from a prior study. Consecutive bacteremic patients were identified over the same period. Procalcitonin and other common measures of inflammation were measured. Descriptive statistics and univariate logistic analyses were performed. Results: Ninety-two study subjects were recruited. Erythrocyte sedimentation rate, C-reactive protein (CRP), and PCT levels were all elevated in bacteremic patients in comparison to the other groups. Erythrocyte sedimentation rate and CRP both had wide ranges that overlapped between groups; however, the PCT concentration was 0.15 μg/mL or greater in 1 of 59 patients with JIA, whereas it was 0.15 μg/mL or less in only 1 bacteremic patient. Conclusions: Our study indicates that serum erythrocyte sedimentation rate, CRP, and PCT levels are all biomarkers that can be used to distinguish SBI versus active JIA at presentation. However, PCT is the most accurate, with the least overlap between patients with infection and noninfectious inflammatory arthritis. This finding can help clinicians direct therapy.